معيارا القصدية والمقامية في علم النص وتطبيقاتهما في القصص القرآني : دراسة وصفية تحليلية - أحمد، منال زكي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The research seeks to reveal what scholars achieved in their studies besides lexical, grammatical, deliberative and semantic levels through the standard Intentionality and Situationality. It is based on the integration between textuality studies and ancient heritage studies. Although ancient scholars differed from modernists on this methodological aspects, the scholars agreed with the contemporaries in some similarities with standards of Intentionality and Situationality, also the ancient heritage opinion in the concepts of Linguistics of Textuality. In the end, the researcher followed the influence of the two standards in understanding Quranic stories, according to the intention of the speaker and his conditions as well. The search was coordinated through two main approaches: First, the descriptive approach by which the researcher described the standard Intentionality and Situationality according to Textuality Linguistics, while rooting these criteria in grammatical, linguistic and rhetorical studies, as well as fundamentalism like the ancient scholars. By taking the information from its sources, and then re-extrapolate them, we can know the opinions of the ancient scholars on concepts, mechanisms, standards of Intentionality and the Situationality. They were then employed in the analysis. The proposed methodology included the analytical approach for standards on Intentionality and Situationality and also, their components in the Quranic stories. The study obtained significant results, the most important: It was the first textual study of Arab and Muslim scholars, but they did not carry out independent study in their books, except briefly. Although it did not live up to the general theory, the research also found that Pronunciational context helped recipients to understand Quranic stories, according to Intentionality standard, especially the presumption of expressions and their meanings, prepositions, additions, adjectives, and status or distinctions; where we find an impact in understanding the events of Quranic stories. Besides, the researcher found that the explanatory standard Situationality was read with constant association with renewed knowledge acquired in humans. Therefore, the researcher believes that the standard mechanism Situationality contributes to textual studies across all linguistic and non-linguistic sciences, such as geography, history, psychology, philosophy, and physics; to enrich the texts and to be understood by the recipients. Finally, the researcher found that the Quranic stories varied in which there is connectivity between the linguistic and non-linguistic sciences in the field of linguistics of traditional and contemporary texts. This consequently, helped to develop an approach or methodology for standard Intentionality and Situationality in the analysis of Quranic.